PELATIHAN PEMBUATAN PANGANAN DARI BUAH MANGROVE JENIS BRUGUIERA GYMNORRHIZA DI PULAU MAITARA KOTA TIDORE KEPULAUAN - Abdul Motalib Angkotasan; Ardan Samman (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Lindur mangrove fruit (Bruguiera gymnorrhiza) which is traditionally processed into cakes, cakes, mixed with rice, or eaten directly. Food sourced from the Coastal Ecosystem, namely the mangrove fruit of the Lindur type (Bruguiera gymnorrhiza) contains energy and carbohydrates that are pretty high, even surpassing the various types of food sources of carbohydrates commonly consumed by the community such as rice, cassava corn, or sago. The study aims to provide food-making training on Maitara Island, North Tidose District, Tidore Islands City. The service method used is Counseling and Training and Courses in food processing from Lindur fruit. The results showed that Lindur fruit has an average length of 27 cm with an average weight of 45 g. The results of the chemical analysis of lindur fruit were 73.756% water content, 1.246% fat content, 1.128% protein, 23.528% carbohydrates, and 0.342% ash content. The anti-nutritional content of HCN is 6.8559 mg and tannin is 34.105 mg. The manufacturing process consists of several stages, namely collecting mangrove fruit, handling mangrove fruit in the form of peeling, soaking then steaming and grinding to become flour to making various types of snacks from mangrove fruit, namely mangrove fruit fritters and mangrove fruit crackers. Dissemination of the importance of mangrove ecosystems regarding the biological functions of mangrove ecosystems and the process of utilizing mangrove ecosystems.